أثر الترويج الالكتروني على تنشيط السياحة الداخلية: استخدام مواقع التواصل الاجتماعي -دراسة حالة ميدانية للوكالة السياحية لوراج - سوق أهراس - فارس قديري; محمد عبد الله بولبدة (My University, 2023)
Summary: This study aims to know the impact of electronic promotion on activating national tourism by using social media sites, and this is through the use of forms that were distributed to the study community, and taking a sample from the clients of the tourist agency Luraj in Souk Ahras. The study reached results, the most important of which is the existence of a statistically significant effect relationship at the level of moral (α– 0.05) electronic promotion on activating domestic tourism by using social media sites. ............................... الملخص: ‏تهدف هذه الدراسة إلى معرفة أثر الترويج الإلكتروني على تنشيط السياحة الداخلية باستعمال مواقع التواصل الاجتماعي وهذا من خلال الاستعانة بي استمارات تم توزيعها على مجتمع الدراسة، وأخذ عينة من زبائن الوكالة السياحية لوراج بسوق أهراس. ‏ولقد توصلت الدراسة إلى نتائج أهمها وجود علاقة تأثير ذات دلالة إحصائية عند مستوى معنوية (0,05=α)الترويج الإلكتروني على تنشيط السياحة الداخلية باستعمال مواقع التواصل الاجتماعي. .................................... Cette étude vise à connaître l'impact de la promotion électronique sur l'activation du tourisme national en utilisant les sites de médias sociaux, et cela à travers l'utilisation de formulaires qui ont été distribués à la communauté d'étude, et en prélevant un échantillon parmi les clients de l'agence de tourisme Luraj à Souk Ahras. L'étude a abouti à des résultats, dont le plus important est l'existence d'une relation d'effet statistiquement significative au niveau de la promotion électronique morale (α - 0,05) sur l'activation du tourisme intérieur en utilisant les sites de médias sociaux.